A Configurational Analysis of Small and Medium-Sized Enterprises’ Radical Innovations: The Perspective of Dynamic Capabilities - Tang, Shuangshuang; Liao, Shudi; Wang, Lumeng; Chen, Weijing; Guo, Zhiwen (Frontiers in Psychology, 2022)
Adopting a configurational perspective, this study explored the pathways for small and medium-sized enterprises (SMEs) to achieve high levels of radical innovation. On the basis of dynamic capabilities theory, six causal conditions for radical innovation were identified at both external and internal levels—that is, environmental turbulence (i.e., technological and market turbulence) and absorptive capacity (i.e., knowledge base, explorative, transformative, and exploitative learning processes). The results of a fuzzy-set qualitative comparative analysis (fsQCA) of 82 Chinese SMEs identified four solutions for high radical innovation. The six causal conditions interacted interdependently and different combinations of these conditions were equally effective pathways for SMEs to achieve radical innovation. Hence, SMEs could generate radical innovation through flexibly allocating resources and capabilities based on the environmental circumstances. By using the fsQCA method, this study contributes to the related literature with an investigation of the complex causal relationship between environmental turbulence, absorptive capacity, and SMEs’ radical innovation. The results resolve some prior contradictory findings and provide new insights for future research. Other theoretical contributions, practical implications, and directions for future research are also discussed.